S-nitrosylation-mediated activation of a histidine kinase represses the type 3 secretion system and promotes virulence of an enteric pathogen - Dan Gu (Nature Portfolio, 2020)
Vibrio parahaemolyticus causes seafood-borne diarrheal diseases. Here, the authors show that the pathogen uses a histidine kinase to sense host-derived nitrite and downregulate a proinflammatory type 3 secretion system, thus enhancing intestinal colonization and virulence.